Racial Microaggressions and Anti-Racism A Review of the Literature with Implications for School-Based Interventions and School Psychologists - Fu, Rui (School psychology review, 2024)
Many racial-ethnic minoritized individuals are repeatedly exposed to subtle actions reflecting racial slights, termed racial microaggressions (RMAs), which are associated with adjustment problems in early adult and adult populations. Early adolescence represents a unique developmental period when minoritized youth begin their racial-ethnic identity exploration and are subjected to stereotypes and prejudice, thereby making them vulnerable to RMAs. Based upon the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist, a systematic literature search, screening and review of RMA literature focusing on high schoolers and younger youth was conducted and yielded 54 publications. This paper reviewed the publications and identified gaps in the field such as the need for systematic research on early adolescents including the frequency and severity of RMAs and the important contributions of peers, parents and teachers for RMA victims, and the need for more evidence-based programming for middle schoolers. Findings suggest that developing school-based microaggression anti-racism programs is clearly needed for minoritized and White youth